Comparing the Position of Faith in the Ideas of Kierkegaard and Ibn Arabi with Emphasis on the Meccan Revelations - Babakhani, Bizhan; Ardalan, Esmail Bani; Seraj, Seyyed Ali (Journal of History Culture and Art Research, 2017)
Faith and belief as well as ratification and believe in the doctrine have always been regarded as key concepts in Gnostic doctrine either in the field of practical gnosis or theoretical gnosis. Defining faith and the ways to explain it depend on the presupposition that faith should be regarded from the perspectives of two well-known mystics. This research tries to explain faith from the perspective of Muhyiddin Ibn Arabi (the father of theoretical gnosis) and Kierkegaard (the father of Existentialism); it also presents an inferential analysis and phenomenological description. For Ibn Arabi, faith is a knowledge and perception including both spiritual aspect of mysticism and a posterior aspect. This virtue is the performance of beliefs. In this manner, faith is a path through which heart gathers reason and religion. Thus, ratification and belief are the prerequisite to enter the path of theoretical mysticism. Hence, walking in the path is acquirement of the real knowledge. Religion is essential for mysticism and finding truth. On the other hand, Kierkegaardian faith does not presupposes religion and legal ethics; but it goes beyond to a meta-rational and meta-ethical domain. Faith is one of the arenas of human existence. Man should be in love to be able to go beyond reason. It is important to be aware that for Kierkegaard, faith is mostly blessings and mercy of God; it is a gift from God rather than the practice of religious orders, acquisition of spirituality, and achieving truth. Although both moralities and religious affairs are intended, it is mostly in form of life within the community as it is a social contract obliging people to observe collective laws and obligations.